The role of selective cyclooxygenase isoforms in human intestinal smooth muscle cell stimulated prostanoid formation and proliferation. Issue 6 (1998) - Longo, Walter E.; Erickson, Brian; Panesar, Ninder; Mazuski, John E.; Robinson, Sandra; Kaminski, Donald L.
Abstract : Intestinal smooth muscle plays a major role in the repair of injured intestine and contributes to the prostanoid pool during intestinal inflammatory states. Cyclooxygenase (COX), which catalyzes the conversion of arachidonic acid to prostanoids exists in two isoforms, COX-1 and COX-2. The purpose of this study was to determine the relative contributions of COX-1 and COX-2 in the production of prostanoids by human intestinal smooth muscle (HISM) cells when stimulated by interleukin-1β (IL-1β) and lipopolsaccharide (LPS). Furthermore the effects of specific COX-1 and COX-2 inhibitors on the proliferation of smooth muscle cells was also evaluated. Confluent monolayer cultures of HISM cells were incubated with IL-1β or LPS for 0-24 h while control cells received medium alone. PGE2 and PGI2 as 6-keto-PGF1α and LTB4 were measured by a specific radioimmunoassay. COX enzymes were evaluated by Western immunoblotting. Unstimulated and stimulated cells were exposed to the specific COX-1 inhibitor valerylsalicylic acid (VSA) and the COX-2 inhibitors NS-398 and SC-58125. The effects of serum on proliferation were then evaluated in the presence of each of the specific COX inhibitors by incorporation of 3 H-thym idine into DNA. IL-1β and LPS increased both PGE2 and 6-ketoPGF1α in a dose dependent fashion with enhanced production detected two hours following exposure. Neither stimulus stimulated LTB4 release. Immunoblot analysis using isoform-specific antibodies showed that both COX-1 and COX-2 were present constitutively. Furthermore, COX-1 was upregulated by each inflammatory stimulus. In a separate set of experiments cells were pretreated with either the selective COX-1 inhibitor VSA or the selective COX-2 inhibitors NS-398 or SC-58125 prior to treatment with IL-1β or LPS. The COX-1 and COX-2 inhibitors decreased both basal and IL-1β and LPS stimulated prostanoid release. Spontaneous DNA synthesis was present and serum consistently increased proliferation. 3 H-thymidine incorporation, stimulated by serum, was inhibited by both COX-1 and COX-2 inhibitors. This study suggests that the prostanoid response stimulated by proinflammatory agents of gut-derived smooth muscle cells appears to be mediated by both COX-1 and COX-2 enzymes. Proliferation of smooth muscles cells also appears to be influenced by both COX-1 and COX-2.